Loss of Function Glucose-Dependent Insulinotropic Polypeptide Receptor Variants Are Associated With Alterations in BMI, Bone Strength and Cardiovascular Outcomes - Kizilkaya, Hüsün Sheyma; Sørensen, Kimmie Vestergaard; Kibsgaard, Camilla J.; Gasbjerg, Laerke Smidt; Hauser, Alexander S.; Sparre-Ulrich, Alexander Hovard; Grarup, Niels; Rosenkilde, Mette M. (Frontiers in Cell and Developmental Biology, 2021)
Glucose-dependent insulinotropic polypeptide (GIP) and its receptor (GIPR) are involved in multiple physiological systems related to glucose metabolism, bone homeostasis, and fat deposition. Recent research has surprisingly indicated that both agonists and antagonists of GIPR may be useful in the treatment of obesity and type 2 diabetes, as both results in weight loss when combined with GLP-1 receptor activation. To understand the receptor signaling related to weight loss, we examined the pharmacological properties of two rare missense GIPR variants, R190Q (rs139215588) and E288G (rs143430880) linked to lower BMI in carriers. At the molecular and cellular level, both variants displayed reduced G protein coupling, impaired arrestin recruitment, and internalization, despite maintained high GIP affinity. The physiological phenotyping revealed an overall impaired bone strength, increased systolic blood pressure, altered lipid profile, altered fat distribution combined with increased body impedance in human carriers, thereby substantiating the role of GIP in these physiological processes.